1972
DOI: 10.1037/h0032102
|View full text |Cite
|
Sign up to set email alerts
|

Father-child interaction and the intellectual functioning of four-year-old boys.

Abstract: To determine the relationship between paternal child-rearing practices, sex-role preference, and intellectual functioning in young boys, 21 lowerclass and 21 middle-class white fathers were observed at home interacting with their 4-year-old sons. The Stanford-Binet, the Peabody Picture Vocabulary Test, and Brown's It Scale for Children were subsequently administered to the children. In the total sample, the boys' IQ was positively correlated with paternal nurturance, and negatively correlated with paternal res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
26
0

Year Published

1977
1977
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 22 publications
(18 reference statements)
0
26
0
Order By: Relevance
“…Research with fathers has thereby been limited almost exclusively to the handicapped population: a priority of the Early Childhood Research Institute at the Frank Porter Graham Child Development Center is to study the role of fathers of young handicapped children, and other researchers concentrating on fathers of the handicapped include Delaney, 1979;Linder and Chitwood, 1984;Markowitz, 1984;and Vadasy, Fewell, Meyer, Schell, and Greenberg, 1984. There have been exceptions to this emphasis-for instance, the Fatherhood Project of the Bank Street College of Education in New York City, which deals with fathers of non-handicapped children, and a study relevant in this article, Rodin (1972), which investigated the father-child interaction and the intellectual functioning of four-year-old boys. A search of the literature revealed no studies, however, that dealt specifically with fathers of young gifted children.…”
mentioning
confidence: 96%
“…Research with fathers has thereby been limited almost exclusively to the handicapped population: a priority of the Early Childhood Research Institute at the Frank Porter Graham Child Development Center is to study the role of fathers of young handicapped children, and other researchers concentrating on fathers of the handicapped include Delaney, 1979;Linder and Chitwood, 1984;Markowitz, 1984;and Vadasy, Fewell, Meyer, Schell, and Greenberg, 1984. There have been exceptions to this emphasis-for instance, the Fatherhood Project of the Bank Street College of Education in New York City, which deals with fathers of non-handicapped children, and a study relevant in this article, Rodin (1972), which investigated the father-child interaction and the intellectual functioning of four-year-old boys. A search of the literature revealed no studies, however, that dealt specifically with fathers of young gifted children.…”
mentioning
confidence: 96%
“…Both Attitude and Activity Scale scores remained unchanged as age of children increased. Several studies have shown an indirect association between the attitudes of the father and his behavior with his child (Aberle and Naegele, 1952;Elder, 1949;Epstein and Radin, 1975;Gardner, 1943;Radin, 1972). Comparison of scores on both scales showed no significant differences as a function of sex of child.…”
mentioning
confidence: 88%
“…The attitudes of an individual regarding the parenting role, how it should be conducted, the types of values transmitted to children, and the conceptions of role functions are usually considered to 99 be important antecedents that influence actual role performances. Several studies have shown an indirect association between the attitudes of the father and his behavior with his child (Aberle and Naegele, 1952;Elder, 1949;Epstein and Radin, 1975;Gardner, 1943;Radin, 1972). Several studies have shown an indirect association between the attitudes of the father and his behavior with his child (Aberle and Naegele, 1952;Elder, 1949;Epstein and Radin, 1975;Gardner, 1943;Radin, 1972).…”
mentioning
confidence: 99%
“…Pavenstedt, 1965Tulkin, 1968). Second, when comparisons are made of the predictive power of SES compared to the predictive power of actual measurements of the child's home environment, analysis reveals that the majority of predictive vari ance between environment and development is accounted for by the actual proximal measurements; SES adds little or no variance above that accounted for by actual measurements of the child's home environment (Hess and Shipman, 1968;Radin, 1972;Kennedy and Wachs, 1975;Bradley et al, 1977). Finally, h A third form of relationship based on the correlation between the child's genotype and his individual response to selected features of a varied environment (type III correla tion) is beyond all present methods of study (l.ayzer, 1974).…”
Section: Environmental Considerations In the Study O F Organism-envirmentioning
confidence: 99%